2020
DOI: 10.3390/coatings10020120
|View full text |Cite
|
Sign up to set email alerts
|

Production, Preparation and Characterization of Microalgae-Based Biopolymer as a Potential Bioactive Film

Abstract: Six microalgae strains were screened according to their biomass productivity and polymer synthesis, showing biomass productivity between 0.14 and 0.68 g/(L·d) for a 21-day growth period. Extracellular biopolymers from the spent culture media of Nostoc sp. (No), Synechocystis sp. (Sy), and Porphyridium purpureum (Pp) was obtained, and the yields of the clean biopolymer were 323, 204, and 83 mg/L, respectively. The crude biopolymer was cleaned up using a solid-phase extraction technique. The emulsification index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…Hence, biodegradable films and coating have been proposed as an environmental friendly alternative to synthetic packaging to preserve the environment and fulfill specific requirements to protect perishable food products and extend their shelf-life (Díaz-Montes & Castro-Muñoz, 2021a). Many studies have reported the efficacy of active films and coatings as quality preservers of many food products (e.g., vegetables, fruits, animal, and dairy) (Aloui & Khwal-dia, 2016;Díaz-Montes et al, 2021a,b;Morales-Jiménez et al, 2020). Depending on the nature of the polymeric matrix and the type of incorporated bioactive compound, active films and coatings can delay microbial growth, preserve food nutritional, physicochemical and sensory properties, maintain initial product's active compounds, confer improved or new bioactivity and increase food shelf-life (Aloui et al, 2021;.…”
Section: Effect Of Active Compounds From Olive Byproducts On Properti...mentioning
confidence: 99%
“…Hence, biodegradable films and coating have been proposed as an environmental friendly alternative to synthetic packaging to preserve the environment and fulfill specific requirements to protect perishable food products and extend their shelf-life (Díaz-Montes & Castro-Muñoz, 2021a). Many studies have reported the efficacy of active films and coatings as quality preservers of many food products (e.g., vegetables, fruits, animal, and dairy) (Aloui & Khwal-dia, 2016;Díaz-Montes et al, 2021a,b;Morales-Jiménez et al, 2020). Depending on the nature of the polymeric matrix and the type of incorporated bioactive compound, active films and coatings can delay microbial growth, preserve food nutritional, physicochemical and sensory properties, maintain initial product's active compounds, confer improved or new bioactivity and increase food shelf-life (Aloui et al, 2021;.…”
Section: Effect Of Active Compounds From Olive Byproducts On Properti...mentioning
confidence: 99%
“…An edible film or coating is any material with a thickness of less than 0.3 mm [ 18 ], which is formed from a combination of biopolymers and different additives ( Section 3.2 ) dispersed in aqueous media [ 19 , 20 , 21 ]. Some authors use the terms of edible film and coating interchangeably; however, others consider that there is a distinction due to the techniques of incorporation into the food product [ 22 ].…”
Section: Edible Films and Coatings As Packing Materialsmentioning
confidence: 99%
“…Edible materials were produced after the incorporation of microalgae with other biopolymers. To achieve that, the whole microalgal cell could be used or compounds could be extracted such as protein concentrates from Spirulina platensis or Chlorella vulgaris (de Oliveira et al., 2018; Moghaddas Kia et al., 2018; Morales‐Jiménez et al., 2020; Stejskal et al., 2020; Tais Cardoso et al., 2017).…”
Section: Food Byproduct Originsmentioning
confidence: 99%